تكنولوجيا المعلومات و دورها في تعزيز رأس المال البشري باعتباره موردا استراتيجيا لتحقيق الميزة التنافسية - غــريـب, الدكتورة: مــنـية (Sciences de l'Homme et de la Société; Vol. 15 (2015): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ(Juin), 2015)
تتبنى أغلب المنظمات في وقتنا الحالي مبدأ الاهتمام بالبشر كأحد المؤثرات القوية التي تعطيها مـيزة تنافسية، خاصةً مع دخول القرن الواحد والعشرين والذي يرتكز على اقتصاد المعرفة، ويعتـبر أن إنتاجية رأس المال البشري هي المحك الرئيس للمحافظة على أي منظمة ناجحة في السوق وأسـاس أي اقتصاد ناجح في العالم. حيث أصبحت القـوة الدافعة لتلك المنظمات هي الأفـراد ذوي المعـرفة، والذكاء، والمهارات التي تتلاءم مع متطلبات القرن الحالي. كل هذا يحتم ضرورة توافر معلومات كافية، صحيحة ودقيـقة عن العنصر البـشري حتى يصبح من الممكن زيادة فاعليته وتطويره مما يكسب المنظمات ميزة تنافسية في السوق.   Abstract :     Most organizations adopt at the present time the principle of interest in human beings as one of the powerful effects that give them a competitive advantage, especially with the entry of the twenty-first century, Especially with the entry of the twenty-first century, which is based on the knowledge economy, and that the productivity of human capital is a key test for the province to any successful organization in the market and the basis of any successful economy in the world. All this makes it imperative to have  adequate, true and accurate information about the human element, so it becomes possible to increase his effectiveness and development, which earns organizations a competitive advantage in the marketplace.